The fate of proximally excluded iliac arteries following open repair of abdominal aortic aneurysms - Dube, Bhekifa (Department of Surgery, 2016)
Aneurysms occur throughout the length of the aorta, with a large proportion occurring in the infra-renal segment of the abdominal aorta (least 9 to 10 times more common than thoracic aortic aneurysms). Aneurysmal disease of the aorto-iliac segment which commonly occurs as a result of a degenerative process is invariably a progressive entity. Concomitant iliac artery aneurysms have been noted to occur in 15-40% of patients with abdominal aortic aneurysms (AAAs). As a result, following open AAA repair, there is a concern regarding the progressive enlargement of the iliac arteries. The aim of this study was to investigate the long term outcome of proximally excluded common iliac arteries (CIAs) following open bifurcated abdominal aortic aneurysm (AAA) repair. Baseline clinical and demographic data of 165 consecutive patients undergoing open AAA repair between April 2004 and April 2014 was collected. The aorta and iliac segments were measured in the 120 available preoperative Computed Tomographic (CT) angiograms. A single postoperative CT scan was performed and measurements recorded in 46 patients available for follow-up. The patients were grouped according to the type of surgical repair, open tube graft repair or bifurcated graft repair to the common iliac (CIA), external iliac artery (EIA) or common femoral artery (CFA). Entered into the study were 165 patients (133 men, 32 women) with a mean age of 66 years and a mean AAA diameter of 6.7cm (range 5.1 - 10.3cm). After a median follow-up of 49 months, 46 patients (88 CIAs) were available for a single postoperative CT scan.